2023
DOI: 10.3390/diagnostics13030439
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram (ECG)-Based User Authentication Using Deep Learning Algorithms

Abstract: Personal authentication security is an essential area of research in privacy and cybersecurity. For individual verification, fingerprint and facial recognition have proved particularly useful. However, such technologies have flaws such as fingerprint fabrication and external impediments. Different AI-based technologies have been proposed to overcome forging or impersonating authentication concerns. Electrocardiogram (ECG)-based user authentication has recently attracted considerable curiosity from researchers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These include the need to provide better quality ECG recordings, the need to develop more advanced deep learning models that can extract significant features from ECG data, the need to adopt secure data transmission protocols such as encryption and SSL (Secure Socket Layers), which can help protect the transmitted data, and the need to implement multifactor authentication, which requires multiple forms of identification in order to access the system (apart from the ECG, the system should require passwords or security tokens, facial image, fingerprints, etc.). It would be extremely important to regularly update and test the ECG-based deep learning authentication system to ensure its effective operation and satisfactory security [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the need to provide better quality ECG recordings, the need to develop more advanced deep learning models that can extract significant features from ECG data, the need to adopt secure data transmission protocols such as encryption and SSL (Secure Socket Layers), which can help protect the transmitted data, and the need to implement multifactor authentication, which requires multiple forms of identification in order to access the system (apart from the ECG, the system should require passwords or security tokens, facial image, fingerprints, etc.). It would be extremely important to regularly update and test the ECG-based deep learning authentication system to ensure its effective operation and satisfactory security [22].…”
Section: Resultsmentioning
confidence: 99%
“…Valvular diseases [11] Left ventricular hypertrophy [12] Onset of atrial fibrillation [13,14] Risk of sudden cardiac death [15] Biological age of the patient [16] Concentration of sex hormones [17] Heart transplant rejection [18] Cardiovascular complications of liver transplantation [19] Effects of cardiac resynchronization therapy [20] Pulmonary embolism [21] Identity verification [22]…”
Section: Subject Of Interest Reference Numbermentioning
confidence: 99%
“…Vision technology [ 39 , 40 ] can identify different users through physical activity characteristics captured from image frames using high-resolution cameras, but it may easily fail in the conditions of luminous changes and obstacles placed in line-of-sight (LoS) [ 4 ], in particular raising severe user privacy concerns. Bioelectrical technology [ 41 , 42 , 43 , 44 ] can utilize bioelectrical sensors, e.g., electrocardiogram (ECG), electromyogram (EMG) and electroencephalogram (EEG), to precisely extract unique biomedical information through body’s electrical activities. Ashraf et al [ 45 ] propose a fusion system that uses biometric features of the iris and foot.…”
Section: Related Workmentioning
confidence: 99%
“…The study contends that a set of vital metabolites aids in the differentiation of paediatric brain tumours. In another work by the authors in [9], several models were used including VGG-16, ResNet-50, and EfficientNet-B0. During comparative analysis, it was observed that EfficientNet-B0 outperforms the other models, yielding an accuracy of 98.8%.…”
Section: Literature Reviewmentioning
confidence: 99%